ICSI does not increase the cumulative live birth rate in non-male factor infertility. Issue 7 (12th June 2018) - Li, Z; Wang, A Y; Bowman, M; Hammarberg, K; Farquhar, C; Johnson, L; Safi, N; Sullivan, E A
Abstract: STUDY QUESTION: What is the cumulative live birth rate following ICSI cycles compared with IVF cycles for couples with non-male factor infertility? SUMMARY ANSWER: ICSI resulted in a similar cumulative live birth rate compared with IVF for couples with non-male factor infertility. WHAT IS KNOWN ALREADY: The ICSI procedure was developed for couples with male factor infertility. There has been an increased use of ICSI regardless of the cause of infertility. Cycle-based statistics show that there is no difference in pregnancy rates between ICSI and IVF in couples with non-male factor infertility. However, evidence indicates that ICSI is associated with an increased risk of adverse perinatal outcomes. STUDY DESIGN, SIZE, DURATION: A population-based cohort of 14 693 women, who had their first ever stimulated cycle with fertilization performed for at least one oocyte by either IVF or ICSI between July 2009 and June 2014 in Victoria, Australia was evaluated retrospectively. The pregnancy and birth outcomes following IVF or ICSI were recorded for the first oocyte retrieval (fresh stimulated cycle and associated thaw cycles) until 30 June 2016, or until a live birth was achieved, or until all embryos from the first oocyte retrieval had been used. PARTICIPANTS/MATERIALS, SETTING, METHODS: Demographic, treatment characteristics and resulting outcome data were obtained from the Victorian Assisted Reproductive Treatment Authority. Data items in the VARTA dataset were collected from all fertility clinics in Victoria. Women were grouped by whether they had undergone IVF or ICSI. The primary outcome was the cumulative live birth rate, which was defined as live deliveries (at least one live birth) per woman after the first oocyte retrieval. A discrete-time survival model was used to evaluate the cumulative live birth rate following IVF and ICSI. The adjustment was made for year of treatment in which fertilization occurred, the woman's and male partner's age at first stimulated cycle, parity and the number of oocytes retrieved in the first stimulated cycle. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 4993 women undergoing IVF and 8470 women undergoing ICSI had 7980 and 13 092 embryo transfers, resulting in 1848 and 3046 live deliveries, respectively. About one-fifth of the women (19.0% of the IVF group versus 17.9% of the ICSI group) had three or more cycles during the study period. For couples who achieved a live delivery, the median time from oocyte retrieval to live delivery was 8.9 months in both IVF (range: 4.2–66.5) and ICSI group (range: 4.5–71.3) ( P = 0.474). Fertilization rate per oocyte retrieval was higher in the IVF than in the ICSI group (59.8 versus 56.2%, P < 0.001). The overall cumulative live birth rate was 37.0% for IVF and 36.0% for ICSI. The overall likelihood of a live birth for women undergoing ICSI was not significantly different to that for women undergoing IVF (adjusted hazard ratio (AHR): 0.99, 95% CI: 0.92–1.06). For couples with a known cause of infertility, non-male factor infertility (female factor only or unexplained infertility) was reported for 64.0% in the IVF group and 36.8% in the ICSI group ( P < 0.001). Among couples with non-male factor infertility, ICSI resulted in a similar cumulative live birth rate compared with IVF (AHR: 0.96, 95% CI: 0.85–1.10). LIMITATIONS, REASONS FOR CAUTION: Data were not available on clinic-specific protocols and processes for IVF and ICSI and the potential impact of these technique aspects on clinical outcomes. The reported causes of infertility were based on the treating clinician's classification which may vary between clinicians. WIDER IMPLICATIONS OF THE FINDINGS: This population-based study found ICSI resulted in a lower fertilization rate per oocyte retrieved and a similar cumulative live birth rate compared to conventional IVF. These data suggest that ICSI offers no advantage over conventional IVF in terms of live birth rate for couples with non-male factor infertility. STUDY FUNDING/COMPETING INTEREST(S): No specific funding was received to undertake this study. There is no conflict of interest, except that M.B. is a shareholder in Genea Ltd. TRIAL REGISTRATION NUMBER: N/A.